A Web Learning Model Integrated with Case Study for College Student Self-Awareness - Muhammad Sahudra, Tengku; Kiswanto Kenedi, Ary; ., Asnawi; Ramadhani, Dini; ., Hamimah; Mardin, Asna (Journal of Ecohumanism, 2024)
The low level of disaster self-awareness among college students served as the driving force for this research, which involved developing a web learning model integrated with a case study that has been deemed valid by experts. This study aimed to identify the web learning model that was integrated into a case study on college students' disaster self-awareness. This study used a nonequivalent control group design in a quasi-experimental setting. This study examined 120 college students in total. According to the research findings from the independent sample t-test calculation, the sig value 0 .000 was lower than 0.05. These findings demonstrated that there was a difference between college students who studied using the web-learning model integrated case study and those who studied using conventional learning models in terms of average disaster self-awareness. The average disaster self-awareness score of college students who used the web-learning learning model integrated case study was greater than that of students who studied conventionally which supported this conclusion. This result showed that raising college students' self-awareness of disasters using a web-learning model integrated with a case study was successful. The research's implications may serve as a guide for improving university students' awareness of disasters.